Effect of fitness training encompassing gymnastics-oriented program of six weeks duration on performance of volleyball players - Ibrahim, S.; Hassanain, M.; Ahmed, S. A.; Ahmed, S. M.; Ahmed, S. K. (Journal of Sports Medicine & Doping Studies, 2018)
The main purpose of the present study was to find out the effect of six weeks of gymnastic oriented training program on the physical fitness and the level of technical performance of Volleyball players. A group of 27 Volleyball players were divided into 12 experimental and 15 control groups and their age ranged between 18 to 24 years. Physical Fitness tests comprising of vertical jump, push-ups, chin ups, sit ups, back strength, 30 m sprint, boomerangs test, 600 m run, sit and reach, bridge up and shoulder rotation and technical skill tests like passing, spiking and service were used for the study. A pre and post test was conducted before starting the training program and after the 6 weeks. It was found that both the physical fitness and skill level of the Volleyball players increased through the participation in the gymnastics oriented program.